Profitability Performance of New Private Sector Banks - An Empirical Study - Bharathi, N. (Indian Journal of Finance, 2010)
Banks play an active role in the economic development of a country. Their ability to make a positive contribution in igniting the process of growth depends on the effective banking system. These banks mostly deal with money collected in the form of deposits along with their own funds in the form of share capital and resources constituting around 5% of the total resources of the banks. So the banks have the obligation of meeting the demand of the customers promptly, paying interest for the amount and meeting the expenses to carry out its activities. This necessitates the banks to maintain adequate liquidity and earn required profit from their activities. Maintenance of liquidity and profitability are contradictory in nature. (Therefore, the banks have to perform the difficult task of maintaining equilibrium between liquidity and profitability). The maintenance of liquidity is necessary to prove the fact that the bank is able to meet its commitments without fail and is paying the day to day expenses. Thus, liquidity refers to the ability of the concern to fulfill its obligations promptly. Whereas, profitability is primarily the measure of the overall success of business and so, it is the ability to earn profit. Profitability is the most powerful motivational factor in any business. The larger the profit, the more efficient and profitable a business is deemed to be. It is the engine that drives a business concern. It also enables a concern to discharge its obligation to the various segments of the society.